2018
DOI: 10.33085/jdg.v1i2.3073
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Kepatuhan Konsumsi PMT Balita dengan Perubahan Status Gizi Balita di Puskesmas Pucangsawit Surakarta

Abstract: Backgorund; Nutritional problems are often associated with less food, especially in infants. Government efforts to deal with nutritional problems among infants are by providing additional food. There are two factors that influence nutritional status, which are direct factors and factors that are irrelevant. Parental compliance behavior in educating their children and complying with government programs is one of the indirect factors that influence nutritional status. The prevalence of malnutrition in 2017 at Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
1
0
6
Order By: Relevance
“…7 The age of toddlers is mostly around 24.80 months, this age is a period of fast growth and development, starting to be easily exposed to infection and physically active, so their daily nutritional needs need to be met. 9 The nutritional status of children Supplementary feeding aims to increase nutritional intake which ultimately can improve nutritional status. 12 In this study, it was found that there were differences in the nutritional status of toddlers before being given PMT-Recovery and after 3 months after being given PMT-Recovery.…”
Section: Resultsmentioning
confidence: 99%
“…7 The age of toddlers is mostly around 24.80 months, this age is a period of fast growth and development, starting to be easily exposed to infection and physically active, so their daily nutritional needs need to be met. 9 The nutritional status of children Supplementary feeding aims to increase nutritional intake which ultimately can improve nutritional status. 12 In this study, it was found that there were differences in the nutritional status of toddlers before being given PMT-Recovery and after 3 months after being given PMT-Recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Balita termasuk kelompok rawan gizi, sehingga zat gizi yang diperlukan lebih besar daripada kelompok usia yang lain. Untuk pemberian makan balita berada pada masa transisi dari makanan bayi ke makanan dewasa,tidak memperoleh pola asuh yang kurang baik karena ibu bekerja atau balita mempunyai adik, sudah mulai bermain dengan lingkungan di sekitarnya sehingga memungkinkan mereka terkena infeksi dan balita belum dapat memilih makanan sendiri (Adelasanti and Rakhma, 2018) (Kesehatan, 2018a). Kabupaten Maros merupakan salah satu kabupaten yang ada di Sulawesi Selatan dengan angka prevalensi stunting 34.87% terdiri dari pendek dan sangat pendek (Riskesdas Sulawesi Selatan, 2018).…”
Section: Pendahuluanunclassified
“…Kepatuhan mengonsumsi makanan tambahan secara tepat mendukung pemenuhan kecukupan asupan gizi yang diiringi dengan konsumsi makanan utama yang cukup. Sebuah studi yang memberikan PMT biskuit modifikasi tepung ikan lele dumbo di Sukabumi menunjukkan bahwa tingkat kepatuhan konsumsi biskuit memiliki hubungan yang signifikan dengan status gizi (Adelasanti & Rakhma, 2018).…”
Section: Hasil Dan Pembahasanunclassified